Clustering and genetic differentiation of the normocyte binding protein (nbpxa) of Plasmodium knowlesi clinical isolates from Peninsular Malaysia and Malaysia Borneo - Ahmed, M.A.; Fong, M.Y.; Lau, Y.L.; Yusof, R. (BioMed Central, 2016)
Background: The zoonotic malaria parasite Plasmodium knowlesi has become an emerging threat to South East Asian countries particular in Malaysia. A recent study from Sarawak (Malaysian Borneo) discovered two distinct normocyte binding protein xa (Pknbpxa) types of P. knowlesi. In the present study, the Pknbpxa of clinical isolates from Peninsular Malaysia and Sabah (Malaysian Borneo) were investigated for the presence of Pknbpxa types and natural selection force acting on the gene. Method: Blood samples were collected from 47 clinical samples from Peninsular Malaysia (n = 35) and Sabah (Malaysian Borneo, n = 12) were used in the study. The Pknbpxa gene was successfully amplified and directly sequenced from 38 of the samples (n = 31, Peninsular Malaysia and n = 7, Sabah, Malaysian Borneo). The Pknbpxa sequences of P. knowlesi isolates from Sarawak (Malaysian Borneo) were retrieved from GenBank and included in the analysis. Polymorphism, genetic diversity and natural selection of Pknbpxa sequences were analysed using DNAsp v 5.10, MEGA5. Phylogentics of Pknbpxa sequences was analysed using MrBayes v3.2 and Splits Tree v4.13.1. The pairwise F ST indices were used to determine the genetic differentiation between the Pknbpxa types and was calculated using Arlequin 3.5.1.3. Results: Analyses of the sequences revealed Pknbpxa dimorphism throughout Malaysia indicating co-existence of the two types (Type-1 and Type-2) of Pknbpxa. More importantly, a third type (Type 3) closely related to Type 2 Pknbpxa was also detected. This third type was found only in the isolates originating from Peninsular Malaysia. Negative natural selection was observed, suggesting functional constrains within the Pknbpxa types. Conclusions: This study revealed the existence of three Pknbpxa types in Malaysia. Types 1 and 2 were found not only in Malaysian Borneo (Sarawak and Sabah) but also in Peninsular Malaysia. A third type which was specific only to samples originating from Peninsular Malaysia was discovered. Further genetic studies with a larger sample size will be necessary to determine whether natural selection is driving this genetic differentiation and geographical separation.